A Museographic Update of the China-Japan Collection of the Real Academia de Bellas Artes de Santa Isabel de Hungría of Seville - García, Macarena Torralba (Mirai. Estudios Japoneses, 2024)
This article examines the China-Japan collection organised by the Japanologist Fernando García Gutiérrez, now at the Real Academia de Bellas Artes de Santa Isabel de Hungría in Seville. It documents the transfer of the exhibition from the original room to where it is currently on display. It also provides an updated museographic and museological analysis. Before addressing this topic, we reflect on the nature of the ensemble and its relationship with specific museological currents, where the question is raised as to whether or not the analysis can be classified as belonging to Oriental Museography.